THE STORY OF YOUNG PHOTOGRAPHER IN “MESATYA – TELUSUR PUPUTAN BADUNG” DOCUMENTARY FILM - Bumiarta, Made Rai Budaya; I Ketut, Muka; I Wayan, Suardana (Institut Seni Indonesia Denpasar, 2024)
Documentary films are a medium for crafting a message and getting that message out to the broader community. The philosophical value of cultural roles and responsibilities can be presented through visual and verbal messages, and documentaries are one of the most accessible digital educational media. The presentation of the documentary Mesatya – Telusur Puputan Badung is a historical story that happened in 1906. It was inspired by the National Museum of Badung royal heritage collection, which the Dutch confiscated during the Military Expedition in 1906. This film depicts Bali with its beautiful nature and culture and the story of the bloody tragedy that ever happened to maintain self-respect and country. Focuses on sequences described in terms of the opening, central, and closing scenes, including the cultural and inspiring values presented in the film through visual and linguistic information. Also, most visuals of Mesatya – Telusur Puputan Badungdocumentary film represented a reconstruction photography technique. We can see that the story runs from the perspective of a young photographer who wants to find inspiration from the event. Audiences are invited to enjoy every shot and scene with a visual aesthetic full of meaning. We can see a detailed description of the meaning of the photographer's journey.